Abused : surviving sexual assault and a toxic gymnastics culture - Haines, Rachel (Gymnast) (Rowman & Littlefield, 2019)
Two-year-old Rachel Haines didn<U+2019>t know that she would be committing to twenty-one years of hard work, dedication, and perseverance as she jumped into the foam pit during her first “mommy and me” gymnastics class. She had no idea that one day she would become a two-time National Team Member, two-time National Champion, and a Division I college gymnast at the University of Minnesota. Nor could she have known that she had just signed herself up for serious injury, emotional distress, and continuous sexual assault by world-renowned trainer turned serial molester, Larry Nassar. In Abused: Surviving Sexual Assault and a Toxic Gymnastics Culture, Rachel details her experiences as a competitive gymnast and the painful realities of being one of Nassar<U+2019>s many victims. With honesty and candidness, Rachel shares how the sport she loved that gave her so much<U+2014>friendships, accomplishments, a college education<U+2014>is also tangled in a dangerously toxic culture that needs to be fixed. In a world that was setting her up for a lifetime of recovery, she tells how faith, family, and an army of survivors made healing possible.